Makna dan Fungsi Makanan Tradisional Jawa: Pendekatan Antropologi Linguistik dan Semiotika - Maulana, Moh. Faiz; Alnizar, Fariz; Amanulloh, Naeni (Universitas Andalas, 2025)
This article examines the meanings and functions of Javanese traditional food through a linguistic anthropological lens. Food is approached not merely as a biological necessity, but as a cultural artifact embedded with social significance. Drawing on a corpus of traditional food names compiled by Endang Nurhayati (2013), this study analyzes how naming practices reflect the cultural logic and symbolic values of Javanese society. The findings demonstrate that the meanings and functions of traditional foods are flexible and contingent upon their socio-cultural contexts, whether in ritual ceremonies or everyday consumption. Naming conventions are shaped by sensory attributes (such as color, taste, texture, and form), sound symbolism (onomatopoeia), and acronyms. These linguistic strategies reveal how language mediates cultural understanding and expresses identity, history, and communal values. The study contributes to broader discussions on the role of food in semiotic systems and the intersection between language, culture, and social practice in Javanese tradition.